Pemberdayaan Masyarakat Berbasis Enterpreneurship pada Usaha Tani Perkotaan - Muhammad Iqbal Usman; Muhammad Ihsan Said Ahmad; Muhammad Hasan; Nurjannah Nurjannah; Nurdiana Nurdiana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to determine community empowerment based on entrepreneurship in urban farming and analyze the efforts that can be made by agricultural extension workers, the government in developing KWT Anggrek. This study uses a qualitative approach. Data collection techniques in the form of observation methods, interviews and documentation. The results of this study indicate that community empowerment at KWT Anggrek has been well implemented, marked by assistance from the government, collaboration, provision of counseling which is always provided by extension workers so that the community can develop and increase agricultural output both in terms of quality and quantity.